Spatial Pattern of Bathymetry in Wangi-Wangi Island and Its Surrounding Based on GEBCO Data and Nautical Map - Yulius, Yulius; Salim, H L; Ramdhan, M (Universitas Muhammadiyah Surakarta, 2015)
The study aims is to define bathymetry based on General Bathymetric Chart of the Oceans (GEBCO) and Nautical Map using GIS technique. The methods used in this study are the kriging method which combines the spatial correlation among the data using GIS and Remote Sensing software. The result shows that bathymetry at research area can be divided into five classes, these are: (1) 0-2 meter with area of 1.797,61 hectare, (2) 2-5 meter with area of 2.059,06 hectare, (3) 5-10 meter with area of 1.184,02 hectare, (4) 10-25 meter with area of 3.025.00 hectare, (5) 25-200 meter with area of 5.648.62 hectare.The spatial pattern of bathymetry dispersed from the shallow water at the edge of beach and more deep at the offshore, except at the eastern side of Wangi-Wangi island which has barrier reef and created basin between them.